GRAMATIKA KASZËBSCZÉGÒ JÃZËKA HANNY MAKURAT – GŁOS W DYSKUSJI - JOCZ, LECHOSŁAW (Slavia Occidentalis, 2020)
This article is yet another contribution to a discussion on a grammar handbook on Kashubian written by Hanna Makurat (2016) and, directly, a reply to her text published in edition 53 of the SFPS. First and foremost, it is a presentation of the history of the discussion of Gramatika… in a context of extra-content strategies employed by the author in the dispute that has arisen. Next, 13 linguistic phenomena have been presented (related to spelling, phonetics, morphology, vocabulary and syntax) in relation to which Hanna Makurat clearly referred to her opponents’ criticism in her text published in the SFPS. An analysis has shown that in 12 of them, the reviewers’ comments were fully justified. Last but not least, general and methodological issues are touched upon with reference to grammar itself and the discussion of it to date.